2022
DOI: 10.1021/acsami.2c16217
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Biomimetic Mineralization of Bone-Like Hydroxyapatite in Hydrogel for the Acceleration of Bone Regeneration

Abstract: A critical-sized bone defect, which cannot be repaired through self-healing, is a major challenge in clinical therapeutics. The combination of biomimetic hydrogels and nano-hydroxyapatite (nano-HAP) is a promising way to solve this problem by constructing an osteogenic microenvironment. However, it is challenging to generate nano-HAP with a similar morphology and structure to that of natural bone, which limits the improvement of bone regeneration hydrogels. Inspired by our previous works on organic–inorganic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…14 Besides improving the compressive resistance, 15,16 the incorporation of inorganic nanoparticles, often in the form of calcium phosphates, would also enhance the bone repair effect of hydrogels. 15−18 Common mineralization methods include in situ mineralization, 18,19 simulated body fluid mineralization, 20 enzymatic mineralization, etc. 21−23 Enzymatic mineralization is involved in regulation through alkaline phosphatase, which induces the nucleation and growth of phosphate and calcium ions in calcium glycerophosphate solution inside the hydrogels to form hydroxyapatite nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Besides improving the compressive resistance, 15,16 the incorporation of inorganic nanoparticles, often in the form of calcium phosphates, would also enhance the bone repair effect of hydrogels. 15−18 Common mineralization methods include in situ mineralization, 18,19 simulated body fluid mineralization, 20 enzymatic mineralization, etc. 21−23 Enzymatic mineralization is involved in regulation through alkaline phosphatase, which induces the nucleation and growth of phosphate and calcium ions in calcium glycerophosphate solution inside the hydrogels to form hydroxyapatite nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Mineralization is one of the most commonly used methods to enhance the stiffness and strength of hydrogels . Besides improving the compressive resistance, , the incorporation of inorganic nanoparticles, often in the form of calcium phosphates, would also enhance the bone repair effect of hydrogels. Common mineralization methods include in situ mineralization, , simulated body fluid mineralization, enzymatic mineralization, etc. Enzymatic mineralization is involved in regulation through alkaline phosphatase, which induces the nucleation and growth of phosphate and calcium ions in calcium glycerophosphate solution inside the hydrogels to form hydroxyapatite nanoparticles. , Compared with simulated body fluid mineralization and in situ mineralization, the strength enhancement of hydrogels through enzymatic mineralization is dramatic. For example, in situ mineralization of chitosan/PVA hydrogels only increased the ultimate tensile stress from 240 to 290 kPa, whereas enzymatic mineralization of polyacrylamide could increase the ultimate tensile stress from 0.8 to 2.4 MPa …”
Section: Introductionmentioning
confidence: 99%
“…The composition and structure of Hydroxyapatite (HA) microscaffolds are similar to the inorganic phase of natural bone and teeth, and has a wide range of applications in the biomedical field. [7][8][9][10] However, the weak osteoinductivity of HA makes it difficult to activate biological processes required for high efficiency bone regeneration. [11] Bone regeneration involves simultaneous activation and complex interaction between the angiogenic and osteogenic pathways, which critically determines the osteoinductivity of implant materials.…”
Section: Introductionmentioning
confidence: 99%
“…HA contains calcium ions that can stimulate the Wnt5A/Ca + pathway and calcium cascade, thereby regulating osteoclastic and osteoblastic activities . The osteo-immunomodulatory effects of biomimetic HA coating on decellularized extracellular matrix hydrogel were investigated by Liang et al They demonstrated that HA could enhance anti-inflammatory factors, resulting in the upregulation of genes associated with osteoblastic differentiation and improved bone regeneration by mimicking bone structure and mineralization. Additionally, HA microparticles ranging from 1 to 30 μm induced the secretion of IL1, IL6, and TNF by immune cells .…”
Section: Introductionmentioning
confidence: 99%